Arts, culture and community development - Meade, Rosie; Shaw, Mae (Rethinking community development., 2021)
Drawing on international examples, this book interrogates the relationship between the arts, culture and community development. Contributors from six continents, reimagine community development as they consider how aesthetic arts contribute to processes of peacebuilding, youth empowerment, participatory planning and environmental regeneration.